An Ascoli theorem for sequential spaces - Gert Sonck (International Journal of Mathematics and Mathematical Sciences)
Ascoli theorems characterize precompact subsets of the set of morphisms between two objects of a category in terms of equicontinuity and pointwise precompactness, with appropriate definitions of precompactness and equicontinuity in the studied category. An Ascoli theorem is presented for sets of continuous functions from a sequential space to a uniform space. In our development we make extensive use of the natural function space structure for sequential spaces induced by continuous convergence and define appropriate concepts of equicontinuity for sequential spaces. We apply our theorem in the context of C*-algebras.